Fault tolerant control for switched linear systems - Du, Dongsheng; Jiang, Bin; Shi, Peng; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book presents up-to-date research and novel methodologies on fault diagnosis and fault tolerant control for switched linear systems. It provides a unified yet neat framework of filtering, fault detection, fault diagnosis and fault tolerant control of switched systems. It can therefore serve as a useful textbook for senior and/or graduate students who are interested in knowing the state-of-the-art of filtering, fault detection, fault diagnosis and fault tolerant control areas, as well as recent advances in switched linear systems.
Fault Detection for Discrete-Time Switched Systems with Interval Time-Varying Delays -- Fault Detection for Discrete-Time Switched Systems with Intermittent Measurements -- Fault Detection for Continues-Time Switched Systems under Asynchronous Switching -- Sensor Fault Estimation and Accommodation for Discrete-Time Switched Systems -- Sensor Fault Estimation and Compensation for Switched Systems with State Delay -- Fault Estimation for Nonlinear Continuous-Time Switched Systems -- Actuator Fault Estimation and Accommodation for Discrete-Time Switched Systems -- Active Fault Tolerant Control for Switched Systems with Time Delay -- Fault Estimation and Accommodation for Switched Systems with Time-Varying Delay -- Observer-Based Reliable Control for Discrete Time Switched Systems -- Conclusions and Future Research Direction.
Electronic reproduction.
Keywords: Linear control systems; Fault tolerance (Engineering); Switching theory; Electronic books